2020
DOI: 10.1136/jitc-2019-000432
|View full text |Cite
|
Sign up to set email alerts
|

SOD3 induces a HIF-2α-dependent program in endothelial cells that provides a selective signal for tumor infiltration by T cells

Abstract: BackgroundTumor-infiltrating lymphocytes (TILs), mainly CD8+ cytotoxic T lymphocytes (CTL), are linked to immune-mediated control of human cancers and response to immunotherapy. Tumors have nonetheless developed specific mechanisms that selectively restrict T cell entry into the tumor microenvironment. The extracellular superoxide dismutase (SOD3) is an anti-oxidant enzyme usually downregulated in tumors. We hypothesize that upregulation of SOD3 in the tumor microenvironment might be a mechanism to boost T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 56 publications
5
47
0
Order By: Relevance
“…In mouse tumor models, LAMA4 levels correlated positively with TIL density after SOD3 overexpression; in contrast, LAMA4 and TIL were reduced after endothelial HIF-2α deletion or WNT pathway inhibition. 6 These data support LAMA4 as a SOD3 mediator for TIL infiltration.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…In mouse tumor models, LAMA4 levels correlated positively with TIL density after SOD3 overexpression; in contrast, LAMA4 and TIL were reduced after endothelial HIF-2α deletion or WNT pathway inhibition. 6 These data support LAMA4 as a SOD3 mediator for TIL infiltration.…”
mentioning
confidence: 65%
“…4 We reported that perivascular SOD3 triggers a program that simultaneously induces vascular normalization and T cell infiltration, thus linking these two processes unequivocally. 5,6 The anti-oxidant enzyme SOD3 is usually downregulated in tumors, which suggests that its loss is advantageous for cancer progression. 7 SOD3 catalyzes the dismutation of the superoxide radical (•O 2 − ) in the extracellular space; this activity not only prevents oxidative damage of lipids or proteins but also preserves the bioavailability of nitric oxide (NO).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SOD3 is known as a predominant form of SODs in plasma [ 10 ]. In many studies, it has been shown that SOD3 is mainly expressed in endothelial cells [ 11 , 26 , 27 ], and its decrease was associated with vascular endothelium damage and the infiltration of inflammatory cells [ 5 , 10 , 28 ]. In our previous study [ 29 ], we demonstrated an increased concentration of endothelium damage markers in AP patients which could be associated with decreased SOD3 concentration in the plasma of these patients.…”
Section: Discussionmentioning
confidence: 99%